The omega-3 postbiotic trans-10-cis-15-octadecadienoic acid attenuates contact hypersensitivity in mice through downregulation of vascular endothelial growth factor A - Saika, Azusa; Nagatake, Takahiro; Kishino, Shigenobu; Kitamura, Nahoko; Honda, Tetsuya; Hosomi, Koji; Tiwari, Prabha; Node, Eri; Kawai, Soichiro; Kondo, Saki; Ishida, Kei; Kabashima, Kenji; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Intestinal bacteria metabolize dietary substances to produce bioactive postbiotics, among which some are recognized for their role in promoting host health. We here explored the postbiotic potential of two omega-3 α-linolenic acid–derived metabolites: trans-10-cis-15-octadecadienoic acid (t10,c15-18:2) and cis-9-cis-15-octadecadienoic acid (c9,c15-18:2). Dietary intake of lipids rich in omega-3 α-linolenic acid elevated levels of t10,c15-18:2 and c9,c15-18:2 in the serum and feces of mice, an effect dependent on the presence of intestinal bacteria. Notably, t10,c15-18:2 mitigated skin inflammation in mice that became hypersensitive after exposure to 2,4-dinitrofluorobenzene, an experimental model for allergic contact dermatitis. In particular, t10,c15-18:2—but not c9,c15-18:2—attenuated ear swelling and edema, characteristic symptoms of contact hypersensitivity. The anti-inflammatory effects of t10,c15-18:2 were due to its ability to suppress the release of vascular endothelial growth factor A from keratinocytes, thereby mitigating the enhanced vascular permeability induced by hapten stimulation. Our study identified retinoid X receptor as a functional receptor that mediates the downregulation of skin inflammation upon treatment with t10,c15-18:2. Our results suggest that t10,c15-18:2 holds promise as an omega-3 fatty acid–derived postbiotic with potential therapeutic implications for alleviating the skin edema seen in allergic contact dermatitis–induced inflammation.